Effect of replacement of de-oiled rice bran with sweet potato leaf meal on growth performance, digestive enzyme activity and body composition of Labeo rohita (Hamilton, 1822) - Ahmad, Ziahan; Deo, Ashutosh Dharmendra; Kumar, Sarvendra; Ranjan, Amit; Aklakur, Md; Sahu, Narottam Prasad (Indian Journal of Fisheries, 2019)
A 60-days feeding experiment was conducted to evaluate the utilisation of sweet potato leaf meal (SPLM) for replacement of de-oiled rice bran (DORB) in the diets of rohu Labeo rohita (Hamilton, 1822) fingerlings. SPLM has good protein content (22.12%) and digestible energy content (11.81 MJ kg-1). Five iso-nitrogenous (30%) and iso-caloric diets (13.5 MJ kg-1) were prepared by replacing DORB with sweet potato leaf meal (SPLM) at 0% (C), 25% (T1), 50% (T2), 75% (T3) and 100% (T4). Each dietary treatment was tested in triplicates with 12 fingerlings per tank, following completely randomised design. The growth performance and feed utilisation parameters viz., weight gain % (WG), specific growth rate (SGR), protein efficiency ratio (PER) and feed conversion ratio (FCR) were not significantly different (p>0.05) among treatments. The digestive enzyme activity remained unaffected except amylase activity, which increased significantly in 50% SPLM replacement group (T2). Chymotrypsin decreased significantly (p<0.05) in the treatment groups. Metabolic enzymes viz., ATPase activity of liver increased significantly (p<0.05) whereas ALP (alkaline phosphatase) activity in the intestine had irregular pattern. The present study indicates that DORB can be completely replaced by SPLM without affecting growth performance and digestive enzyme activity in the diet of L. rohita.